EFFECTIVE METHODS OF TEACHING ENGLISH THROUGH EDUCATIONAL TECHNOLOGIES AND ARTIFICIAL INTELLIGENCE - Zoxidova Sevinch Zoxid qizi (TALABALAR ILMIY KONFERENSIYASI "TILSHUNOSLIK MASALALARI – YOSH TADQIQOTCHILAR NIGOHIDA", 2025)
In this article, you will read about the easy and effective ways of teaching English through educational technologies and artificial intelligence in today's modern world. In addition, you will learn about the benefits of artificial intelligence in language learning.